Effect of acupuncture compared with placebo-acupuncture at P6 as additional antiemetic prophylaxis in high-dose chemotherapy and autologous peripheral blood stem cell transplantation: a randomized controlled single-blind trial - Streitberger, Konrad; Friedrich-Rust, Mireen; Bardenheuer, Hubert J.; Unnebrink, Kristina; Windeler, Jürgen; Goldschmidt, Hartmut; Egerer, Gerlinde (Clinical cancer research, 2003)
PURPOSE: The purpose is to investigate an additional antiemetic effect to ondansetron with needle acupuncture at P6 compared with nonskin-penetrating placebo acupuncture in patients undergoing high-dose chemotherapy and autologous peripheral blood stem cell transplantation. - EXPERIMENTAL DESIGN: Eighty patients who were admitted to hospital for high-dose chemotherapy and autologous peripheral blood stem cell transplantation were included into a randomized placebo-controlled single-blind trial. The patients were randomized to receive acupuncture (n = 41) or noninvasive placebo acupuncture (n = 39) at the acupuncture point P6 30 min before first application of high-dose chemotherapy and the day after. All patients received 8 mg ondansetron/day i.v. as basic antiemetic prophylaxis. The main outcome measure was the rate of patients who either had at least one episode of vomiting or required any additional antiemetic drugs on the first 2 days of chemotherapy. - RESULTS: The main outcome measure showed no significant difference (P = 0.82): 61% failure in the acupuncture group and 64% in the placebo acupuncture group (95% confidence interval of 3% difference: -18.1 and 24.3%). Comparing nausea, episodes of vomiting or retching and number of additionally required antiemetic drugs did not provide any discrepancy with the main result. - CONCLUSIONS: This study suggests that in combination with ondansetron i.v., invasive needle acupuncture at P6 compared with nonskin-penetrating placebo acupuncture has no additional effect for the prevention of acute nausea and vomiting in high-dose chemotherapy.